Desenvolvimento de linguiça suína, cozida e defumada, com adição de biomassa de banana verde e redução dos teores de sódio e gordura - Thomé, Bruna Rodrigues (2017)
Food consumption patterns have changed according to concerns regarding environmental sustainability, regional development, nutritional aspects and, mainly, health issues. The results on changing this habit involve demand growth and the need for food that, besides nourishing the organism, can also offer other healthy qualities. Therefore, meat products have become the objects of many scientific studies, which, mainly, concern their nutritional composition. The usage of replacements for fat, such as the green banana biomass (GBB), is an alternative that can be sought in order to create this appeal for the consumers. The GBB is a kind of food that can be added to several formulations without altering their original taste. It also has many nutritional advantages, like the presence of fiber and resistant starch in it. However, there are not studies that use the GBB in cooked pork sausage. Because of this, this study aims to make cooked and smoked pork sausage with added green bananas biomass and to reduce its sodium and fat levels. For this purpose, three formulations were developed: Control and Treatment (TC), without adding the green bananas biomass and without reducing the sodium and fat levels; Treatment 1 (T1), by adding 2,17% of GBB and reducing the sodium and fat levels in 15%; and Treatment 2 (T2), with added 3,12% GBB and a reduction of 20% on sodium level and 30% on fat levels. Physicochemical, microbial and sensory analysis have been carried out in three different times: one day after processing (t0), seven days after processing (t7) and twenty-one days after processing (t21), and these analyses aimed to check possible alterations, over time during storage, under refrigeration. We concluded, through the obtained results, that the developed product, with added GBB and reduction on its sodium and fat levels, was in accordance to the current physicochemical and microbial regulation standards, during the storage time. As for the sensory analysis, excepting the scent aspect, we concluded that all other aspects did not present statistical differences. The T2 treatment was the most indicated one among the evaluated aspects.